A Commentary on the Council of Europe Convention on Action against Trafficking in Human Beings - Helmut Sax (Elgar Commentaries series, 2020)
This comprehensive Commentary provides the first fully up-to-date analysis and interpretation of the Council of Europe Convention on Action against Trafficking in Human Beings. It offers a concise yet thorough article-by-article guide to the Convention's anti-trafficking standards and corresponding human rights obligations.